The Pre-service Teachers' Source of Anxiety in Online Teaching Practice during Covid-19 Outbreak - Wardana, Septian Tri; Asari, Slamet; Asmara, Candra Hadi (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
<a title="Pre-service Teachers' Source of Anxiety in Online Teaching Practice during Covid-19 Outbreak" href="https://docs.google.com/document/d/1Bx7V1VqkqoQXgDfrT01GSJnFKXgaS3ve/edit?usp=drivesdk&ouid=109738052001300680651&rtpof=true&sd=true">https://docs.google.com/document/d/1Bx7V1VqkqoQXgDfrT01GSJnFKXgaS3ve/edit?usp=drivesdk&ouid=109738052001300680651&rtpof=true&sd=true